(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The boom of quality in last two decades of the XXth century is associated with ISO 9000 standards. Their three quality assurance models, offered the possibility toobtain an international recognition to the organization’s commitment with quality:the ISO 9000 certification. In the face of the imminent review of these standards, this paper analyses the present and future of certification and its peaceful coexistence with schemes of recognition based on management excellence models like EFQM. This is the case of European Excellence Seals, which reward all those organizationsthat make an effort to integrate Excellence in their management systems.